Loreto Day School, Sealdah - Sharma, Rajeev, (SAGE Knowledge. Cases., 2017)
In 1979 the Loreto School, Sealdah, located in Calcutta, had more than 700 students of which 90 were from the lower socio-economic strata and unable to pay their fees. These 90 students were part of a free primary school, which had been merged with the main school several years earlier. The failure rate among children of poor economic backgrounds was high and as a result their drops out rates were also very high. Any child who failed class V was removed from the school by the parents, which was the case for about half of the students. It was at this juncture that the management appointed a new principal, Sister Cyril. Perturbed by the existing situation, she decided to address the problems. First of all, the teachers were guided to help the academically weak students by using alternative teaching methods or organising remedials. Secondly, parents were helped to understand that failure in examinations did not mean that children should discontinue their school education. Due to concerted efforts of principal and teachers, there was a change in the attitude of both teachers and parents; the drop-out rate decreased and student performance increased gradually.